The effects of Task-Oriented Motor Training on gait characteristics of patients with type 2 diabetes neuropathy - Salsabili, Hoda (J Diabetes Metab Disord, 2016)
BACKGROUND: It is known that general gait training improves lower extremity muscle strength and endurance in Diabetes Neuropathy (DN). But, it is still unknown whether Task-Oriented (TO) gait training would change gait biomechanics and the risk of falling in DN. TO gait training focuses on promoting timing and coordination of lower extremity movements through goal-directed practices with sufficient repetition. METHODS: A group of 14 patients with DN participated in a time-series study. All subjects participated in four sessions of assessments (Initial, Pre, Post and Follow-Up). Training was twice a week for 12 weeks. Vertical and horizontal Ground Reaction Forces (GRF), Time Get up and Go (TGUG) and Fall Efficacy Scale-International (FES-I) were evaluated. Gait training started with stepping patterns that progressively changed to complicated patterns of walking. Then, training continued combining walking patterns with upper extremity activities and then ended with treadmill-paced practice. RESULTS: DN patients significantly increased Second Vertical Peak Force and Horizontal Propulsive Force in addition decrease in Minimum Vertical Force. TGUG significantly decreased while FES-I reflected significant increase after gait training. DISCUSSION: Conclusively, training not only improved gait performance, confidence in daily activities and attenuated risk of falling, but also helped DN patients to improve feet biomechanics, muscles timing and coordination. CONCLUSIONS: Gait training with respect to principles of motor learning allowed patients to effectively improve through sessions.